ADAPTED SOLUTION WITH NEWTON-KANTOROVICH METHOD FOR NONLINEAR VOLTERRA INTEGRAL EQUATIONS - AMINA, KHIRANI (Université de M'sila, 2018)
Find an approximate solution is one of the most important problems in our days, in this paper we look for an approximate solution for Volterra nonlinear integral equation using a combination between Newton-Kantorovich method and adapted trapezoidal method. Then we do a comparaison between the numerical results obtained by this method against ones obtained by another authors.
Keywords: Nonlinear Volterra integral equation, Newton- Kantorovich method, adapted trapezoidal method